The Fascinating Animal Book for Kids : 500 Wild Facts! - Clarke, Ginjer L. (Emeryville, California : Rockridge Press, 2021)
From anteaters to zebras-incredible facts packed with pictures Are you a budding zoo keeper or veterinarian, or are you just WILD about animals? Everything that animal books for kids ages 9-12 should be, The Fascinating Animal Book for Kids is packed with colorful photos and 500 ferocious facts about creatures from all over the world. Unlike other animal books for kids ages 9-12, all the super cool facts inside are organized by type of animal, so you can quickly find the critters you want to study. Animal books for kids ages 9-12 should be fun and educational. In this one, youll learn super cool facts like: Snow leopards keep themselves warm by wrapping their tails around their bodies like scarves. Fireflies use their lights to talk to each other. Immortal jellyfish can live forever. They grow to adulthood and then shrink back to babies, over and over again.
Keywords: Animals -- Miscellanea; Juvenile literature; Zoology -- Juvenile literature; Curiosities and wonders -- Juvenile literature; Trivia and miscellanea